Sistem Rekomendasi Pakaian Muslim Toko Al-Fath Semarang Dengan Collaborative Filtering - Nadila Dara Rahmawati; Agus Prasetyo Utomo (Elkom: Jurnal Elektronika dan Komputer, 2022)
The many variations of Muslim clothing make customers confused in determining which clothes to buy. One solution is to use a recommendation system that can help customers find clothes according to their wants and needs. This study aims to create a product recommendation system that can provide product recommendations to Muslim clothing stores using the collaborative filtering method. The recommendation results will only display a maximum of 6 Muslim clothes that have been seen or purchased based on the similarity value of the highest Muslim clothing to the recommendation level with the lowest similarity. The results of Muslim clothing recommendations from customer A are Queen Dress (P0007) with a similarity value of 2.00, Trimuji Toyobo (P0006) with a similarity value of 1.40, Wonder Set 3in1 (P0008) with a similarity value of 1.00, Afnan Atasan Tunik (P0009 ) with a similarity value of 1.00 and Abaya Embroidery Maxi (P0010) with a similarity value of 1.00